Harnessing Information and Communication Potentials for Effective Healthcare Delivery and Promotion in the 21st Century Nigeria - Umeakuka, Okey A. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The purpose of this paper is to identify and exploit the potentials of information and communication in order to achieve effective and functional healthcare delivery and promotion in Nigeria. To achieve this purpose, the paper discussed the themes under an Introduction, Healthcare Delivery Services in Nigeria, Health Promotion and Healthcare Delivery Service, Information and Health Information in Healthcare Delivery and, Communication and Health Communication, Patient Education in Healthcare Delivery and Promotion, and Information and Communication Technology (ICT) Applications in Healthcare Practice. Conclusions were drawn from expositions and some recommendations made such as that the government at all levels should endeavour to provide the 21st century health facilities since the governments control the resources of the land and should be able to afford the expensive facilities.